Do we really need vestibular and proprioceptive cues for homing - Bülthoff, H. H.; Riecke, B. E.; Veen, H. A. H. C. van (Invest. Ophthalmol. Vis. Sci. (ARVO), 2000)
Purpose: The literature generally suggests that even for simple navigation tasks, optic flow information is insufficient, and proprioceptive or vestibular cues are required. To test this claim, we conducted triangle completion experiments in a virtual environment providing optic flow information only. Methods: All experiments were performed in a simulated 3D field of blobs providing a convincing feeling of self-motion but no landmarks, thus restricting navigation strategies to optic flow based path integration. Ego-motion was visually simulated on a half-cylindrical 180$^°$ projection screen of 7m diameter using mouse buttons for locomotion control. In Exp 1, subjects had to execute turns and reproduce distances using randomized given velocities. Exp's 2 and 3 were triangle completion experiments: Subjects had to return to the starting point after moving outwards along two prescribed segments of the triangle. In Exp 2, five different isosceles triangles for left and right turns were used. In Exp 3, 60 different triangles were used, with length of leg 1, leg 2 and the enclosed angle randomized. Results: In all experiments, we found a linear correlation between executed and correct turns or distances, quantified by the slope of the fit (compression rate) and the signed error. In Exp 1, untrained subjects executed distances and turns with negligible systematic errors, irrespective of movement velocity. Exp 2 revealed no signed error for distance or turn response. Subjects showed a strong tendency towards mean responses for distances (slope 0.58), but not for turns (0.91). In Exp 3, performance was enhanced for distances (0.86), but reduced for turns (0.77). Conclusions: Visual path integration by optic flow proved to be reliable and sufficient for simple navigation tasks. Compared to similar triangle completion experiments using virtual environments (Péruch et al., Perc. 97; Duchon et al., Psychonomics 99) or blind locomotion (Loomis et al., JEP 93), we did not find the typically observed strong compression (slope <0.5) towards mean turn responses. We also found fewer systematic errors. In our experiments, vestibular and proprioceptive cues were not needed for accurate homing.
Keywords: Riecke; Riecke_2000; bernhard-riecke; iSpaceWeb; journalPaper